Determining the Target of Independent Graduation for Beneficiary Families of the Hopeful Family Program - Andre Argisitawan; Widyastuti Andriyani; Bambang Purnomosidi DP; Dommy Kristomo (Journal of Intelligent Software Systems, 2022)
The Family Hope Program (Program Keluarga Harapan) or better known as PKH is the conditional social assistance to the Poor Families which are designated as PKH Beneficiary Families. Self-Graduation is one of the goals of the PKH program, Self-Graduation is a condition in which the PKH Beneficiary Families is declared ‘passed’ from PKH participation with their respective awareness. This recommendation system uses the Simple Additive Weighting (SAW) method to calculate the criteria for several website-based alternatives with the Model View Controller concept.